Pre-lithiation method based on magnetron sputtering and application

The formation of a uniform lithium metal film on the battery substrate through magnetron sputtering technology has solved the problems of uneven preparation and low compatibility in the existing prelithiation technology, and achieved prelithiation of high-energy density lithium-based batteries.

CN119517925APending Publication Date: 2025-02-25JILIN UNIVERSITY
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411641426.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing prelithiation technology is difficult to achieve uniform and controllable preparation, and it is not compatible with multiple battery systems, which poses problems such as safety hazards and low compatibility of manufacturing processes.

Method used

The prelithiation method based on magnetron sputtering is adopted, and a uniform lithium metal film is formed on the substrate through magnetron sputtering technology, and the lossless transfer is carried out in combination with the glove box to achieve effective control of the thickness of the prelithiated layer.

Benefits of technology

The uniformity and controllability of prelithiated materials are achieved, the overall capacity and energy density of the battery are improved, and compatible with a variety of battery systems, avoiding the impact of air on the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119517925A_ABST
    Figure CN119517925A_ABST
Patent Text Reader

Abstract

The invention discloses a pre-lithiation method based on magnetron sputtering and application, and belongs to the field of batteries, and the pre-lithiation method comprises the following steps: S1, cutting a base material to be pre-lithiated into a required size for later use in advance; s2, the cut base material is placed on an objective table in a magnetron sputtering working chamber, a cabin door is closed, a vacuum pump is started, the interior of equipment is vacuumized, when the internal pressure reaches a fixed value A, argon is introduced at a certain gas flow, and the angle of a gate valve is adjusted to enable the internal pressure to be kept at a fixed value B; then, all sputtering parameters are set and recorded, and the base material is subjected to pre-lithiation; and S3, the base material subjected to magnetron sputtering pre-lithiation is subjected to lossless transfer through a glove box, and the influence of air on the pre-lithiation material is avoided. The method not only can be compatible with various battery systems, but also can effectively control the process, so that the pre-lithiation efficiency is greatly improved. In addition, the pre-lithiated material can be transferred in a lossless manner through a glove box, so that the influence caused by air is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of batteries, and in particular relates to a pre-lithiation method based on magnetron sputtering and the use of the method for a high energy density lithium-based battery. Background Art

[0002] As society gradually develops towards intelligence and high-end development, the proportion of new energy in the energy structure continues to increase. Especially in recent years, the rapid development of the new energy vehicle industry has further promoted the innovation of the energy industry. Lithium-ion batteries have been widely used in various fields due to their excellent cycle performance, extremely high energy density and excellent energy conversion efficiency.

[0003] In a conventional battery structure, all mobile lithium ions initially come from the cathode material, while the anode material contains no lithium ions before the first charge (known as "formation"). However, in subsequent cycles, a portion of the active lithium ions in the cathode cannot be transferred. This is mainly because when a lithium-ion battery is charged for the first time, the formation of the solid electrolyte interface film consumes a large amount of lithium ions provided by the positive electrode, resulting in a low coulombic efficiency in the first cycle and a significant decrease in available capacity. In addition, as the cycle progresses, some active lithium ions may lose their activity due to the growth of the solid electrolyte interface film and the deposition of lithium metal, further reducing battery performance.

[0004] To solve the above problems, researchers have developed a usable technology that introduces additional active lithium ions into the battery to compensate for the loss of lithium, and offsets the initial irreversible lithium loss by replenishing lithium into the battery before it is put into use. This technology effectively reduces the loss of the first irreversible capacity by pre-adding lithium to the electrode material, significantly improving the overall capacity and energy density of the battery. At present, pre-lithiation technology has become an important means to improve the performance of lithium-based batteries.

[0005] However, the pre-lithiation methods currently used are difficult to achieve uniform and controllable preparation, and are not compatible with a variety of battery systems. For example, some methods perform pre-lithiation through direct contact with lithium metal, but this process usually uses excess lithium, which requires removal of excess lithium after pre-lithiation, which not only increases the complexity of the manufacturing process, but also makes the uniformity and controllability of the pre-lithiation amount more difficult. In addition, some chemical pre-lithiation methods, such as immersing the electrodes in highly reducing solutions, will bring safety issues to large-scale battery manufacturing. Electrochemical pre-lithiation requires the pre-lithiation battery to be disassembled and reassembled, which reduces compatibility with current battery manufacturing processes.

[0006] In summary, pre-lithiation technology needs to be further improved to solve the above problems and promote its practical application to realize the next generation of high energy density lithium-based batteries. Summary of the invention

[0007] In view of the problems existing in the existing pre-lithiation technology, such as the difficulty in achieving uniform and controllable preparation, the present invention provides a pre-lithiation method based on magnetron sputtering and its application in high energy density lithium-based batteries. This method is not only compatible with a variety of battery systems, but also can achieve effective control of the process, greatly improving the pre-lithiation efficiency. In addition, the pre-lithiation material can also be transferred losslessly through a glove box to avoid the influence of air.

[0008] In order to achieve the above technical objectives, the present invention adopts the following technical solutions:

[0009] A pre-lithiation method based on magnetron sputtering specifically comprises the following steps:

[0010] S1, cutting the required pre-lithiation substrate into required size for standby use;

[0011] S2. Place the cut substrate on the stage in the magnetron sputtering studio, close the hatch and start the vacuum pump to evacuate the interior of the equipment. When the internal pressure reaches a constant value A, introduce argon gas at a certain gas flow rate and adjust the gate valve angle to keep the internal pressure at a constant value B. Then set and record various sputtering parameters to pre-lithiate the substrate.

[0012] S3. Transfer the substrate pre-lithiated by magnetron sputtering through a glove box without loss to avoid the influence of air on the pre-lithiated material.

[0013] Furthermore, in step S1, the substrate to be pre-lithiated is a positive electrode, a negative electrode or a separator.

[0014] Furthermore, the positive electrode is lithium iron phosphate, lithium nickel cobalt manganese oxide or lithium cobalt oxide; the negative electrode is a graphite carbon-based material, a silicon-based material, lithium metal or copper foil; the diaphragm material includes at least one of polyethylene (PE) or polypropylene (PP), preferably Celgard 2320 diaphragm (three-layer film PP / PE / PP), Celgard 2325 diaphragm (three-layer film PP / PE / PP), Celgard 2400 diaphragm (single-layer film PP) or Celgard 2500 diaphragm (single-layer film PP).

[0015] Furthermore, in step S2, the fixed value A is 9×10 -4 Pa, the fixed value B is 1Pa.

[0016] Further, in step S2, a material containing a lithium source is used as a target material, with a purity of 99.9%, a diameter of 50.8 mm, and a thickness of 5 mm; argon is used as a working gas, with a purity greater than 99.99% and a flow rate of 10-50 sccm;

[0017] The target material used for pre-lithiation is lithium metal target, the distance between the lithium metal target and the substrate is 10-30mm, the sputtering power is 50-150W, and the substrate temperature is room temperature-300℃;

[0018] The sputtering time can be set arbitrarily to achieve controllability of the thickness of the pre-lithiation layer. The thickness of the pre-lithiation layer is preferably controlled at 1-20 μm, and the sputtering rate can be calculated by the sputtering time and the cross-sectional thickness.

[0019] Furthermore, in step S3, magnetron sputtering is combined with a glove box to transfer the sample non-destructively through the door of the glove box.

[0020] Furthermore, in step S3, the water value in the glove box is <0.01ppm, and the oxygen value is <0.01ppm; the inert atmosphere in the glove box is argon gas with a purity greater than 99.99%.

[0021] Furthermore, steps S2-S3 are all completed in a glove box.

[0022] On the other hand, the present invention also provides an application of a magnetron sputtering pre-lithiation method in high energy density lithium-based batteries, which is as follows: assembling a battery with a pre-lithiated substrate to perform an electrochemical performance test and comparing it with a substrate that has not been pre-lithiated.

[0023] Compared with the prior art, the present invention has the following advantages:

[0024] 1. The present invention uses magnetron sputtering technology to achieve the accumulation of lithium metal in the form of atoms on the substrate, thereby quickly and effectively preparing a lithium metal film with a thickness of nanometers or submicrometers as a pre-lithiation layer. The surface of the pre-lithiation material obtained by this method is more uniform and smooth, and the adhesion between the pre-lithiation material and the substrate is also better;

[0025] 2. The present invention can achieve effective control of the thickness of the pre-lithiation layer by adjusting various parameter settings during the magnetron sputtering process, leaving no residue after pre-lithiation, thereby avoiding waste of resources;

[0026] 3. The present invention uses magnetron sputtering to achieve pre-lithiation of each component of the battery, and can be compatible with a variety of battery systems and manufacturing processes;

[0027] 4. The magnetron sputtering and glove box used in the present invention are combined devices. After the sputtering is completed, the pre-lithiation substrate can be transferred without loss to avoid the influence of air on the material. The schematic diagram of the device is shown in Figure 1 . BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the following is a brief introduction to the drawings required for the specific embodiments or the description of the prior art. In all the drawings, similar elements or parts are generally identified by similar reference numerals. In the drawings, the elements or parts are not necessarily drawn according to the actual scale.

[0029] Figure 1 It is a schematic diagram of a device for lossless transfer magnetron sputtering pre-lithiation of the present invention;

[0030] Figure 2 The figure is a comparison of the electrochemical performance of the pre-lithiated lithium iron phosphate electrode of Example 1 and the non-pre-lithiated lithium iron phosphate electrode of Comparative Example 1;

[0031] Figure 3 This is a comparison diagram of the electrochemical performance of the pre-lithiated negative electrode graphite pole piece of Example 2 and the non-pre-lithiated negative electrode graphite pole piece of Comparative Example 2;

[0032] Figure 4 This is the electrochemical performance diagram of the pre-lithiated 2325 separator of Example 3;

[0033] Figure 5 This is the electrochemical performance diagram of the 2325 separator without pre-lithiation in comparative example 3. DETAILED DESCRIPTION

[0034] The technical solution of the present invention will be further described in detail below in conjunction with several embodiments and drawings of the specification. It is worth noting that the embodiments cited are only some embodiments of the present invention. According to the embodiments of the present invention, any other embodiments obtained by ordinary technicians in the field without creative work belong to the protection scope of the present invention. In the following embodiments, experimental methods not specifically described generally follow conventional conditions. The specific embodiments of the present invention are as follows:

[0035] Example 1

[0036] This embodiment provides a method for pre-lithiation of anode materials based on magnetron sputtering, which specifically includes the following steps:

[0037] (1) Preparation of lithium iron phosphate pole piece: lithium iron phosphate: conductive agent Super P: binder polyvinylidene fluoride (PVDF) are thoroughly mixed at a mass ratio of 8:1:1, and then an appropriate amount of N-methylpyrrolidone (NMP) solvent is added and placed on a homogenizer to form a uniform slurry. The slurry is then applied to the current collector aluminum foil, vacuum dried at 80°C overnight, and cut into 12 mm diameter discs for later use.

[0038] (2) Pre-lithiation of lithium iron phosphate pole piece: Place the lithium iron phosphate pole piece on the stage in the magnetron sputtering chamber, close the sputtering chamber door and start the vacuum pump. When the vacuum degree of the chamber reaches 9×10-4 After Pa, the DC magnetron sputtering system can be turned on. Then, argon gas is introduced with a flow rate of 30sccm, and the vacuum degree of the chamber is maintained at 1Pa during the sputtering process by adjusting the angle of the gate valve. Turn on the sputtering power supply, adjust the parameters to form a stable plasma arc: sputtering power 100W, sputtering time 10min, substrate temperature at room temperature, and turn on the sample stage for rotation. After sputtering, the pre-lithiated lithium iron phosphate pole piece is transferred losslessly through the glove box for subsequent battery assembly. According to the cross-sectional thickness test, the thickness of the pre-lithiation layer after sputtering is 5±0.5μm.

[0039] (3) Battery assembly: The battery is assembled in the order of positive electrode shell, gasket, pre-lithiated lithium iron phosphate electrode, electrolyte, diaphragm, electrolyte, lithium metal, gasket, spring, and negative electrode shell. It is then placed on a button battery sealing machine and maintained at a pressure of 60 MPa for 30 seconds. It is then removed and left to stand for a period of time before testing.

[0040] Example 2

[0041] This embodiment provides a method for pre-lithiation of negative electrode materials based on magnetron sputtering, which specifically includes the following steps:

[0042] (1) Preparation of negative electrode graphite pole piece: negative electrode graphite: conductive agent Super P: binder PVDF were mixed thoroughly at a mass ratio of 8:1:1, and then an appropriate amount of NMP solvent was added and placed on a homogenizer to form a uniform slurry. The slurry was then applied to the current collector copper foil, vacuum dried at 80°C overnight, and cut into 12 mm diameter discs for later use.

[0043] (2) Pre-lithiation of negative graphite pole piece: Place the above negative graphite pole piece on the stage in the magnetron sputtering studio, close the sputtering door and turn on the vacuum pump. When the vacuum degree of the chamber reaches 9×10-4Pa, the DC magnetron sputtering system can be turned on. Then, argon gas is introduced with a flow rate of 30sccm. The vacuum degree of the chamber is maintained at 1Pa during the sputtering process by adjusting the angle of the gate valve. Turn on the sputtering power supply and adjust the parameters to form a stable plasma arc: sputtering power 100W, sputtering time 10min, substrate temperature at room temperature, and turn on the sample stage for rotation. After sputtering, the pre-lithiated negative graphite pole piece is transferred non-destructively through the glove box for subsequent battery assembly. According to the cross-sectional thickness test, the thickness of the pre-lithiation layer after sputtering is 5±0.5μm.

[0044] (3) Battery assembly: The battery is assembled in the order of positive electrode shell, gasket, pre-lithiated negative electrode graphite electrode, electrolyte, separator, electrolyte, lithium metal, gasket, spring, and negative electrode shell. It is then placed on a button battery sealing machine and maintained at a pressure of 60 MPa for 30 seconds. It is then removed and left to stand for a period of time before testing.

[0045] Example 3

[0046] This embodiment provides a method for pre-lithiation of a diaphragm based on magnetron sputtering, which specifically includes the following steps:

[0047] (1) Pre-lithiation of 2325 diaphragm: First, cut the 2325 diaphragm into 19 mm diameter discs, then place them on the stage in the magnetron sputtering studio, close the sputtering door and turn on the vacuum pump. When the vacuum degree of the chamber reaches 9×10-4Pa, the DC magnetron sputtering system can be turned on. Then, introduce argon gas with a flow rate of 30sccm, and adjust the angle of the gate valve to maintain the vacuum degree of the chamber at 1Pa during the sputtering process. Turn on the sputtering power supply, adjust the parameters to form a stable plasma arc: sputtering power 100W, sputtering time 10min, substrate temperature at room temperature, and turn on the sample stage for rotation. After sputtering, the pre-lithiated negative graphite pole piece is transferred non-destructively through the glove box for subsequent battery assembly. According to the cross-sectional thickness test, the thickness of the pre-lithiation layer after sputtering is 5±0.5μm.

[0048] (2) Battery assembly: The battery was assembled in the order of positive electrode shell, gasket, lithium metal, electrolyte, pre-lithiated 2325 separator, electrolyte, lithium metal, gasket, spring, and negative electrode shell. It was then placed on a button battery sealing machine and kept at a pressure of 60 MPa for 30 seconds. It was removed and left to stand for a period of time before testing.

[0049] In order to demonstrate the beneficial effects of the present invention, the following comparative examples are set up for comparison with the above embodiments:

[0050] Comparative Example 1

[0051] This comparative example uses a non-pre-lithiated lithium iron phosphate electrode, and compared with Example 1, specifically includes the following steps:

[0052] (1) Preparation of lithium iron phosphate pole piece: lithium iron phosphate: conductive agent Super P: binder PVDF were mixed thoroughly at a mass ratio of 8:1:1, and then an appropriate amount of NMP solvent was added and placed on a homogenizer to form a uniform slurry. The slurry was then applied on the current collector aluminum foil, vacuum dried at 80°C overnight, and cut into 12 mm diameter discs for later use.

[0053] (2) Battery assembly: The battery is assembled in the order of positive electrode shell, gasket, the above-mentioned lithium iron phosphate electrode, electrolyte, diaphragm, electrolyte, lithium metal, gasket, spring, and negative electrode shell. It is then placed on a button battery sealing machine and maintained at a pressure of 60 MPa for about 30 seconds. It is removed and left to stand for a period of time before testing.

[0054] Comparative Example 2

[0055] This comparative example uses a negative electrode graphite pole piece that is not pre-lithiated, and compared with Example 2, specifically includes the following steps:

[0056] (1) Preparation of negative electrode graphite pole piece: negative electrode graphite: conductive agent Super P: binder PVDF were mixed thoroughly at a mass ratio of 8:1:1, and then an appropriate amount of NMP solvent was added and placed on a homogenizer to form a uniform slurry. The slurry was then applied to the current collector copper foil, vacuum dried at 80°C overnight, and cut into 12 mm diameter discs for later use.

[0057] (2) Battery assembly: The battery is assembled in the order of positive electrode shell, gasket, the above-mentioned negative electrode graphite plate, electrolyte, diaphragm, electrolyte, lithium metal, gasket, spring, and negative electrode shell. It is then placed on a button battery sealing machine and maintained at a pressure of 60 MPa for about 30 seconds. It is removed and left to stand for a period of time before testing.

[0058] Comparative Example 3

[0059] This comparative example uses a non-pre-lithiated 2325 separator, and compared with Example 3, specifically includes the following steps:

[0060] First, cut the 2325 diaphragm into 19mm diameter discs for later use. Then assemble the battery in the order of positive electrode shell, gasket, lithium metal, electrolyte, 2325 diaphragm, electrolyte, lithium metal, gasket, shrapnel, and negative electrode shell. Then place it on a button battery sealing machine, keep it at a pressure of 60MPa for about 30s, remove it and let it stand for a while before testing.

[0061] The cycle stability of the pre-lithiation substrates prepared in Examples 1-3 and the batteries assembled with the substrates in Comparative Examples 1-3 were analyzed using the Xinwei battery testing system. The specific parameters of the test steps of Example 1 and Comparative Example 1 were as follows: voltage charge and discharge range 2.5-4V, 0.1C activation for 2 cycles, followed by 3C long cycle test (1C = 170mA·g -1 ), for specific test results, see Figure 2 ;

[0062] The specific parameters of the test steps of Example 2 and Comparative Example 2 are: voltage charge and discharge range 0.01-2V, 0.1C activation for 2 cycles, followed by 1C long cycle test (1C = 372mA·g -1 ), for specific test results, see Figure 3 ;

[0063] The specific parameters of the test steps of Example 3 and Comparative Example 3 are: current density 3mA·cm -2 , cycle capacity 1mAh·cm -2 Carry out long cycle test, see the specific test results Figure 4 and Figure 5 .

[0064] Figure 1The schematic diagram of the magnetron sputtering and glove box combination device involved in the present invention is shown. After the sputtering is completed, the pre-lithiation substrate can be transferred losslessly to avoid the influence of air on the material.

[0065] pass Figure 2-Figure 5 The electrochemical performance comparison shows that the cycle stability of the magnetron sputtering pre-lithiated lithium iron phosphate cathode, negative electrode graphite, and diaphragm has been significantly improved. Figure 2 The capacity of pre-lithiated lithium iron phosphate can still be maintained at 73 mA g after 1000 cycles under 3C conditions. -1 The capacity of lithium iron phosphate that has not been pre-lithiated drops to nearly 0 under the same cycle conditions. Figure 3 The capacity of the pre-lithiated negative electrode graphite was also significantly improved after 500 cycles under 1C conditions. Figure 4 and Figure 5 The polarization curves show that the pre-lithiated 2325 separator has a high conductivity at 3 mA cm -2 &1mAh·cm -2 The cycling stability under the conditions can be extended to 500 hours, while the polarization of the non-pre-lithiation membrane increases sharply when the cycle reaches about 170 hours. The above results all show that the application of magnetron sputtering pre-lithiation technology on the positive electrode, negative electrode and membrane can significantly improve the electrochemical performance of the battery, demonstrating the usefulness of the invention.

[0066] The preferred embodiments of the present invention are described in detail above in conjunction with the accompanying drawings. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0067] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0068] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A pre-lithiation method based on magnetron sputtering, characterized in that: The specific steps include: S1, cutting the required pre-lithiation substrate into required size for standby use; S2. Place the cut substrate on the stage in the magnetron sputtering studio, close the hatch and start the vacuum pump to evacuate the interior of the equipment. When the internal pressure reaches a constant value A, introduce argon gas at a certain gas flow rate and adjust the gate valve angle to keep the internal pressure at a constant value B. Then set and record various sputtering parameters to pre-lithiate the substrate. S3. Transfer the substrate pre-lithiated by magnetron sputtering through a glove box without loss to avoid the influence of air on the pre-lithiated material.

2. A pre-lithiation method based on magnetron sputtering according to claim 1, characterized in that: In step S1, the substrate to be pre-lithiated is a positive electrode, a negative electrode or a separator.

3. A pre-lithiation method based on magnetron sputtering according to claim 1, characterized in that: The positive electrode is lithium iron phosphate, lithium nickel cobalt manganese oxide or lithium cobalt oxide; the negative electrode is graphite carbon-based material, silicon-based material, lithium metal or copper foil; the diaphragm material includes at least one of polyethylene or polypropylene.

4. A pre-lithiation method based on magnetron sputtering according to claim 1, characterized in that: The diaphragm is a Celgard 2320 diaphragm, a Celgard 2325 diaphragm, a Celgard 2400 diaphragm or a Celgard 2500 diaphragm.

5. A pre-lithiation method based on magnetron sputtering according to claim 1, characterized in that: In step S2, the fixed value A is 9×10 -4 Pa, the fixed value B is 1Pa.

6. A pre-lithiation method based on magnetron sputtering according to claim 1, characterized in that: In step S2, a lithium source-containing material is used as a target material, with a purity of 99.9%, a diameter of 50.8 mm, and a thickness of 5 mm; argon is used as a working gas, with a purity greater than 99.99% and a flow rate of 10-50 sccm; The target material used for pre-lithiation is lithium metal target, the distance between the lithium metal target and the substrate is 10-30mm, the sputtering power is 50-150W, and the substrate temperature is room temperature-300℃; The thickness of the pre-lithiation layer is controlled at 1-20 μm, and the sputtering rate can be calculated by the sputtering time and the cross-sectional thickness.

7. A pre-lithiation method based on magnetron sputtering according to claim 1, characterized in that: In step S3, magnetron sputtering is combined with a glove box to transfer the sample non-destructively through the door of the glove box.

8. A pre-lithiation method based on magnetron sputtering according to claim 1, characterized in that: In step S3, the water value in the glove box is <0.01 ppm, and the oxygen value is <0.01 ppm; the inert atmosphere in the glove box is argon gas with a purity greater than 99.99%.

9. A pre-lithiation method based on magnetron sputtering according to claim 1, characterized in that: The steps S2-S3 are all completed in a glove box.

10. Application of a magnetron sputtering pre-lithiation method according to claim 1 in high energy density lithium-based batteries, characterized in that: Specifically, the pre-lithiated substrate is used to assemble a battery for electrochemical performance testing and compared with a non-pre-lithiated substrate.

Citation Information

Patent Citations

  • Method for simply reinforcing large-size magneto-controlled sputter coating

    CN103014645A

  • Novel lithium-pre-intercalated negative plate and preparation method thereof

    CN105244472A

  • PVD nanometer magnetron sputtering silver plating metalization process of ceramic dielectric filter

    CN112647050A

  • Lithium supplementing method for silicon-based negative pole piece of all-solid-state lithium ion battery

    CN114725325A

  • Lithium supplement diaphragm, preparation method thereof, lithium ion battery and lithium supplement method

    CN116598707A